Magnolia x ’Peter Smithers’ ’Peter Smithers’ Magnolia: FPS-365/FP365, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of the ‘Peter Smithers’ magnolia, a deciduous shrub known for its large, light pink flowers that bloom in late winter to early spring. It details the plant’s characteristics, including its upright growth habit, moderate growth rate, and coarse texture. The magnolia thrives in USDA hardiness zones 5 through 9A and can be planted year-round in zones 7 to 9. It is best used as a specimen plant in sunny spots, though it can tolerate partial shade. The document also covers planting and care tips, noting that the tree is generally pest-free but may be affected by scales and leaf spots. Original publication date October 1999.